2006
DOI: 10.1111/j.0902-4441.2006.t01-1-ejh2957.x
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of current vitamin K dosing algorithms for the reversal of over‐anticoagulation with warfarin: the need for a more tailored dosing regimen

Abstract: Appraisal of current vitamin K dosing algorithms for the reversal of overanticoagulation with warfarin: the need for a more tailored dosing regimen Warfarin has long been utilized for the treatment of thromboembolic disorders and its use has escalated further by recent demonstrations that it effectively prevents strokes in atrial fibrillation (1-3); currently about 1% of the UK population receives warfarin and this is increasing. The clinical effectiveness of warfarin is critically dependent upon maintaining t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 47 publications
0
26
0
1
Order By: Relevance
“…Many factors affect vitamin K reversal of VKA anticoagulation [25]. Advanced age may lead to excessive correction by decreasing hepatic clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors affect vitamin K reversal of VKA anticoagulation [25]. Advanced age may lead to excessive correction by decreasing hepatic clearance.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that environmental and genetic factors influence the warfarin dose necessary for therapeutic response. Different studies have confirmed that age and weight are the most consistent variables influencing warfarin variability, even if diet and concurrent medication affect dose requirement [10,11,12,13] . Recently it was shown that some of the unexplained variability in the requirement of warfarin dose depends on variants of 2 genes, CYP2C9 and VKORC1 (according to HUGO nomenclature).…”
Section: Current and Potential Application Of Genomic Biomarkers In Cmentioning
confidence: 99%
“…They are also at higher risk for over-anticoagulation and serious bleeding [14,15,16]. Different common polymorphisms and haplotypes have also been identified in the VKORC1 gene, and some of them have been found to be associated with the variability in warfarin dose requirements, explaining a larger percentage of variability compared to CYP2C9 SNPs [5,10,11,12,17,18,19,20,21,22]. The T allele of VKORC1 1173 C>T SNP (c.173+1000, rs9934438) is highly associated with a low mean weekly warfarin dose (MWWD) while the A allele of VKORC1 3730 G>A SNP (c.492+134, rs7294) is associated with a high MWWD [22].…”
Section: Current and Potential Application Of Genomic Biomarkers In Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Warfarin is one of the most widely used anticoagulants, yet interindividual differences in drug response, a narrow therapeutic range and a high risk of bleeding or thrombosis complicate its clinical use [1][2][3]. Warfarin gains its importance because many people are dependent on this drug (1% of the population in many western countries).…”
Section: Introductionmentioning
confidence: 99%